Emergency Blood Gas Test: an Imperative - Julio César López Arística (Universidad de las Ciencias Médicas de Cienfuegos, 2012)
We must address a topic related to emergency services provided in our municipal intensive care units that were created about nine years ago all over the country. Our current main problem is the lack of gasometers to perform the blood gas test both in arteries and veins as well as ionograms for follow-up of patients in the first six ours after their admission in our centers.